Topological Hall Effect: Emergent Topological Hall Effect at a Charge‐Transfer Interface (Small 50/2020). Issue 50 (17th December 2020) - Lim, Zhi Shiuh; Li, Changjian; Huang, Zhen; Chi, Xiao; Zhou, Jun; Zeng, Shengwei; Omar, Ganesh Ji; Feng, Yuan Ping; Rusydi, Andrivo; Pennycook, Stephen John; Venkatesan, Thirumalai; Ariando, Ariando
Abstract : In aticle number 2004683, Ariando Ariando and co‐workers report that topological Hall effect is found in a CaMnO3 /CaIrO3 /CaMnO3 //LaAlO3 (001) heterostructure, which indicates the presence of magnetic Skyrmions entailing the charge‐transfer induced magnetic superexchange. Thickness variations and atomic structure analyses suggest that the Dzyaloshinskii–Moriya interaction originates from the top CaMnO3 /CaIrO3 interface, but is suppressed at the bottom CaIrO3 /CaMnO3 interface due to the presence of stacking faults.